Life-world mediatization and popular culture - Costa, Vincenzo (Scenari, 2021)
Understanding the relationship between life-world and media is one of the most fascinating and challenging issue of phenomenology. In this contribute, we explored this topic, discussing how the mediatization of comunication transforms the life-world in a mediatizated environment. The mediatization creates a new panorama of the world and changes how people experiences the horizon of their own possibilities, their understanding of the world, himself and others. From this phenomenological point of vieuw we explore the relationship between the media, popular culture e society.